Rancang Bangun Sistem Aplikasi Keuangan Siswa pada SMP Islam Al-Muhajirin Depok - Muhamad Ilham Idris Yunus; Puput Irfansyah; Wahyu Nur Cholifah (Universitas Indraprasta PGRI Jakarta, 2020)
In this globalization era, almost all organizations in many fields demand a quick solution to a problem. Efficient, fast accurate and timely information is certainly needed to increase the productivity, effectiveness and efficiency of an organization. The Islamic Junior High School Al-Muhajirin Depok is one of the organizations engaged in the field of education that has not yet had a special application that manages the financial system for data collection, payment and preparation of student financial reports. The purpose of this research is to design a student financial application system and student financial statements using the Java programming language and research & development methods to develop an effective application, especially for a student financial system. The results of the created system can help the running of a student's financial system, easing the finding of the necessary data and making more effective and more efficient performance of administrative officer.